Analysis of the Relationship Between Female Coaches’ Leadership: Efforts to Support the Achievement of Men’s and Women’s Futsal - Hapsari Pragusti Putri; Nina Sutresna; Berliana; Sendi Cornelia (Universitas Negeri Semarang, 2025)
This study analyzes the relationship between female coaches’ leadership styles and the performance of amateur futsal teams in Bandung, Indonesia. Using the Leadership Scale for Sport (LSS), the research evaluated five leadership dimensions training and instruction, democratic behavior, autocratic behavior, social support, and positive feedback among 87 athletes from 6 clubs coached by female coaches. Team performance was measured based on competition rankings. The results of Pearson correlation and multiple regression analyses indicated that training and instruction, democratic behavior, and social support had a positive influence on team performance (p < 0.05), while autocratic behavior and positive feedback showed a negative trend (p < 0.10), although not statistically significant. These findings suggest that collaborative and supportive leadership approaches enhance athletic performance, whereas authoritarian methods may hinder it. This study highlights the importance of adaptive leadership in sports coaching and provides practical recommendations to improve futsal team success.